The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/erv.2697
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and financial implications of hospital malnutrition in Spain

Abstract: Objective The aim of this review is to analyse the studies about cost and clinical implications that malnutrition causes in the Spanish hospitals. Material and methods The review of the literature was carried out through a bibliographic search in Web of Science following the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) criteria and analyse the cost of treatment of malnourished and anorexia nervosa (AN) patients Results Seventeen studies with economic data related to malnutrition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 52 publications
0
10
0
1
Order By: Relevance
“…TREASURE ET AL. (Ombudsman, 2017, p. 2;Yárnoz-Esquíroz, Lacasa, Riestra, C., & Frühbeck, 2019). Surveys of patients, carers and other stakeholders have established the key ingredients of a highquality ED service, namely well-coordinated care delivered by a knowledgeable and specialist treatment team centred around the patient and their social support (Escobar-Koch, et al, 2010;van Furth, van der Meer, & Cowan, 2016;Hart & Wade, 2019;Nishizono-Maher, Escobar-Koch, & Ringwood, 2010).…”
Section: Highlightsmentioning
confidence: 99%
See 1 more Smart Citation
“…TREASURE ET AL. (Ombudsman, 2017, p. 2;Yárnoz-Esquíroz, Lacasa, Riestra, C., & Frühbeck, 2019). Surveys of patients, carers and other stakeholders have established the key ingredients of a highquality ED service, namely well-coordinated care delivered by a knowledgeable and specialist treatment team centred around the patient and their social support (Escobar-Koch, et al, 2010;van Furth, van der Meer, & Cowan, 2016;Hart & Wade, 2019;Nishizono-Maher, Escobar-Koch, & Ringwood, 2010).…”
Section: Highlightsmentioning
confidence: 99%
“…In Germany, the average increase in diagnoses for one large insurer between 2011 and 2016 was 7.5% (https://www.aerzteblatt.de/nachrichten/ 94751/Essstoerungen-auf-dem-Vormarsch). Late detection and treatment delays are associated with poorer prognosis (Andres-Perpiña et al, 2020;Fernández-Aranda et al, 2020) and increased burden (Yárnoz-Esquíroz et al, 2019) and therefore improving awareness and early diagnosis and access to treatment may reduce the increase in severity illness which has been manifest in the UK in terms of increased bed use (Holland, Hall, Yeates, & Goldacre, 2016).…”
Section: The Care Pathwaysmentioning
confidence: 99%
“…Sarcopenia is recognized as a nutrition-related condition that may be related to the aging process (primary sarcopenia); however, it may also result from pathogenic mechanisms (secondary sarcopenia) that are disease-related, activity-related, or nutrition-related [1]. This all leads to poor outcomes in the health, quality of life, morbidity, and mortality of patients, accompanied by a significant increase in healthcare costs [11,[186][187][188]. For this reason, early detection must be a systematic objective pursued as soon as the relationship is established between the social or the healthcare system and the individual [189,190], as adequate nutritional intervention is shown to reduce mortality and complications in hospitalized patients [191].…”
Section: Discussionmentioning
confidence: 99%
“…An appropriate nutritional intervention, tailored to the individual needs of patients identified as malnourished or at nutritional risk, should be implemented. Unfortunately, although the need for this process is fully acknowledged, it is not systematically implemented [11]; 21,000 patients from 325 hospitals in 25 European countries are included in a study by the "NutriDay" survey, with the results showing that only 52% (ranged between 21% and 73%) of the hospitals in the different regions have a detection routine [12]. Similar results are obtained in a clinical audit to establish the gap between practice and best practice in activities related to nutritional screening and assessment in New South Wales hospitals [13].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in hospitalization rates is one of the main consequences of malnutrition, leading to increased health expenditures [ 19 , 20 ]; however, only the FINES study, which was conducted with a population undergoing dialysis, showed that oral supplementation improved serum albumin and prealbumin levels and hospitalization rates in dialysis patients [ 17 ]. We found no study that evaluated these data in pre-dialysis patients; our study is, therefore, the first that we know of to link lower hospitalization rates to individualized nutritional interventions.…”
Section: Discussionmentioning
confidence: 99%